Environment stimulation workshop with community health agents - experience report (Research, Society and Development, 2023)
It is an experience report of part of an extension project, developed in a multidisciplinary way, from ideation to its execution. It aims to present the holding of training workshops with Community Health Agents, with the theme of using Environmental Stimulation as an intervention strategy for children with typical development or not. The workshops were composed of four modules, with a total duration of two shifts. Here only the module of Occupational Therapy is described. The demand for participation was spontaneous, with online and free registrations. Active methodology was used, prioritizing dialogue and collective construction. As a trigger point, there was the simulation of the environment of a house, with its main rooms (living room, kitchen, bedroom and bathroom), as well as the disposal of everyday objects and toys, industrialized or made of scrap metal. The evaluations were simultaneous and the comments served as reference for the necessary adjustments. As positive feedback were highlighted the dynamics used, which facilitated the exchange of knowledge between participants and a critical analysis of their professional practice, generating new ideas of strategies to intervene in their community, in addition to the recognition of ACS as a knowledge multiplier and team member. The work of the occupational therapist focused on Environmental Stimulation, bringing it as something viable, which can be added to the day-to-day care activities carried out by parents, with known low-cost materials, minimizing the emotional and financial burden of the caregiver, was another differential pointed out.